The last full measure - Damon, Mark, 1933-; Bogart, Timothy Scott; Sanghani, Shaun, 1980-; Cafritz, Nicholas; Peterson, Robert Reed; Robinson, Todd, 1958-; Stan, Sebastian, 1982-; Plummer, Christopher; Hurt, William; Roadside Attractions (Firm) (Roadside Attractions, 2020)
The true story of William Pitsenbarger, an Air Force medic who saved more than sixty men in one of the bleakest battles of the Vietnam War. Presented the chance to escape on the last helicopter, Pitsenbarger stayed behind to save and defend his comrade in arms. Twenty years later, Pitsenbarger's fellow soldiers and father seek the help of investigator Scott Huffman and other surviving veterans to finally secure him The Congressional Medal of Honor he deserved.
Title from sell sheet.
Originally released as a motion picture in 2019.
Wide screen.
Special features: the women of The last full measure ; Medal of Honor Ceremony shoot ; That others may live remembering Operation Abilene ; USAF Museum screening with veterans & Pitsenbarger Family ; the music of The last full measure ; William Pitsenbarger tribute gallery.
Sebastian Stan, Christopher Plummer, William Hurt, Ed Harris, Samuel L. Jackson.
Rating: R.
Keywords: United States. -- Air Force -- Medical personnel -- Drama; Vietnam War, 1961-1975 -- Veterans -- Drama; Medal of Honor -- Drama; War films; Feature films; Video recordings for the hearing impaired